2018
DOI: 10.1101/298075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased green autofluorescence is a marker for non-invasive prediction of H2O2-induced cell death and decreases in the intracellular ATP of HaCaT cells

Abstract: Since oxidative stress plays important pathological roles in numerous diseases, it is of both critical theoretical and clinical significance to search for the approaches for predicting oxidative damage. Cellular models have great value for studying oxidative damage, which would be significantly promoted if non-invasive approaches for predicting oxidative damage can be established without the need of exogenous probes. In our current study, we tested our hypothesis that changes of the autofluorescence (AF) of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The lower ORR is likely due to increased flavin production (riboflavin, flavin mononucleotide, and FAD) during the cellular response to cytotoxic stress, suggesting the ORR [NAD(P)H/(FAD + NAD(P)H)] is sensitive to cell death. 73,74 Interestingly, we found that the mean ORR was independent of organoid area for the PCOs imaged in this study (area range: 0.02 to 0.9 mm 2 ). Larger PCOs exhibited higher mean FAD intensity values due to larger dead cores, but this was compensated by increased NAD(P)H levels at the periphery, which we hypothesize is due to the presence of more viable cell material.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The lower ORR is likely due to increased flavin production (riboflavin, flavin mononucleotide, and FAD) during the cellular response to cytotoxic stress, suggesting the ORR [NAD(P)H/(FAD + NAD(P)H)] is sensitive to cell death. 73,74 Interestingly, we found that the mean ORR was independent of organoid area for the PCOs imaged in this study (area range: 0.02 to 0.9 mm 2 ). Larger PCOs exhibited higher mean FAD intensity values due to larger dead cores, but this was compensated by increased NAD(P)H levels at the periphery, which we hypothesize is due to the presence of more viable cell material.…”
Section: Discussionmentioning
confidence: 52%
“…S4 in the Supplemental Materials). 73,74 Conversely, the intensity of NAD(P)H and FAD increases and decreases, respectively, in the core compared to the rim of hollow organoids. This results in a high ORR in the core of hollow organoids, which do not appear to have an apoptotic core (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 21, 2020. ; https://doi.org/10.1101/2020.12.19.423617 doi: bioRxiv preprint mononucleotide, and FAD) during the cellular response to cytotoxic stress, suggesting the optical redox ratio [NAD(P)H/(FAD + NAD(P)H)] is sensitive to cell death. 58,59 Interestingly, we found that the mean optical redox ratio was independent of organoid area for the PCOs imaged in this study (area range: 0.02-0.9mm ). Larger PCOs exhibited higher mean FAD intensity values due to larger dead cores, but this was compensated by increased NAD(P)H levels at the periphery, Statistical techniques such as mixed-effect effect models can use these time-course data to account for organoid-level heterogeneity and provide improved sensitivity to drug response.…”
Section: Discussionmentioning
confidence: 54%